Design and Force Analysis of the Driving System for Bedrock Drilling - Lujia Li; Zhichuan Zheng (Jixie chuandong)
A new type of driving system for bedrock drilling is proposed. The structure and working principle of the driving system are expounded， and the structure design of the reduction transmission device and the parameter selection are completed. The force analysis of the reduction transmission device is carried out， and the design of the driving system for bedrock drilling is perfected. Finally， dynamics analysis and reliability analysis of the driving system are carried out by using ANSYS Workbench. The results show that the structural design of the driving system for bedrock drilling under polar ice is reasonable.